2021
DOI: 10.51544/jalm.v6i2.2000
|View full text |Cite
|
Sign up to set email alerts
|

Perbandingan Pemeriksaan Tinja Metode Sedimentasi Dengan Metode Natif Dalam Mendeteksi Soil Transmitted Helminth

Abstract: Soil Transmitted Helminth (STH) is the most common intestinal parasific infection and in one of the contributors to the global disease burden. Diagnosis of Soil Transmitted Helminth desease can be done using sedimentation method and natif method. This study aims to find out the differences in sedimentation methods and natif methods in deteting Soil Transmitted Helminth Type of research conducted ind true experimental form. This research was conducted on March 27-29, 2021 at the Microbiology Laboratory of Muham… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
0
1
0
2
Order By: Relevance
“…Research conducted by Lalangpuling (2020) where positive results were obtained as many as 5 respondents or (4%) using the native method (Lalangpuling, 2020). Research conducted by Nurhidayanti and Permana (2021) on the comparison of stool examination with the sedimentation method with the native method in the detection of Soil Transmitted Helminths showed that there was no significant difference between the two methods (Nurhidayanti & Permana, 2021). Table 3 shows that in underweight children, 1 child (2%) had intestinal worms and 3 children (6%) had negative worms.…”
Section: Resultsmentioning
confidence: 99%
“…Research conducted by Lalangpuling (2020) where positive results were obtained as many as 5 respondents or (4%) using the native method (Lalangpuling, 2020). Research conducted by Nurhidayanti and Permana (2021) on the comparison of stool examination with the sedimentation method with the native method in the detection of Soil Transmitted Helminths showed that there was no significant difference between the two methods (Nurhidayanti & Permana, 2021). Table 3 shows that in underweight children, 1 child (2%) had intestinal worms and 3 children (6%) had negative worms.…”
Section: Resultsmentioning
confidence: 99%
“…Berdasarkan hasil secara makroskopik dari 16 sampel dengan ciri-ciri bewarna (cokelat, kuning, hijau), konsistensi (keras, lunak, cair), tidak mengandung bakteri, virus, jamur, parasit, lendir, nanah, darah, dan serat daging yang menandakan hasil normal. Setelah itu dilanjutkan pengamatan secara mikroskopis dengan menggunakan metode natif (Nurhidayanti & Permana, 2021). Prinsip dari metode natif yaitu eosin mengandung zat warna asam yang dapat diserap oleh telur cacing (menghasilkan warna merah pada sitoplasma).…”
Section: Tabel 1 Gambaran Telur Soil Transmitted Helmint (Sth) Pada A...unclassified
“…Rerata metode sedimentasi adalah 6,75 dan rerata metode flotasi adalah 13,56 (19). Penelitian yang dilakukan Nurhidayanti dan Permana menggunakan metode sedimentasi biasa dan natif diperoleh hasil bahwa pada kedua metode pemeriksaan telur cacing ini tidak terdapat perbandingan pada kedua metode hanya saja pada metode sedimentasi lapang pandang di mikroskop lebih jelas dibandingkan dengan metode natif (20).…”
Section: Hasil Dan Pembahasanunclassified